CHILDHOOD STUDIES: INCLUSION WITH EMPHASIS ON OPPOSITIONAL DEFIANT DISORDER - ODD - Nunes Sapori, Aline (Revista Gênero e Interdisciplinaridade, 2023)
The school has no end in itself, it is a living environment and, at the same time, an instrument of access of the subject to citizenship, creativity and autonomy, it is, by its nature and function, an interdisciplinary institution. It is constituted as a process of living and preparing for life; thus, its curricular, pedagogical and didactic organization must consider the plurality of voices, conceptions, experiences, rhythms, cultures, and interests. The present study aims to analyze the way in which the teaching-learning process interferes and facilitates the inclusion and development of students with Oppositional Defiant Disorder (ODD). understand about the disorder and its specificities, examine how the teaching-learning process and inclusion can occur in the classroom with students with ODD. We chose exploratory research, which aims to characterize, classify and define the problem. Bibliographic research, to provide greater familiarity with the problem. And the research modality will be the case study, the most common that focuses on only one institution, in this case the chosen school. The approach was made through qualitative, descriptive research, where the information obtained cannot be quantifiable.